NEUROPATHIC PAIN: CHALLENGES AND SOLUTIONS IN CLINICAL PRACTICE - Mitrović , Vekoslav; Stolić, Radojica; Mitrović , Vladimir (Sanamed, 2025)
Neuropathic pain is caused by abnormal processing of signals in the peripheral and central nervous systems. It is characterized by pain occurring without external stimulation or long after the injury has passed. Typically, it is chronic, with patients describing it as burning, stinging, stabbing, or tingling. Causes include diabetes, herpes zoster, surgery, stroke, multiple sclerosis, tumors, and injuries. Despite significant advances in neuropathic pain research in recent years, therapeutic options remain limited and often insufficiently effective. Symptomatic therapy for neuropathic pain is based on the use of drugs from four basic groups: antidepressants, anticonvulsants, local analgesics, and opioids. In addition to pharmacological methods, non-pharmacological interventions are also used in the treatment of neuropathic pain. A combination of these methods with pharmacological therapy often yields the best results.